Analysis of body difficulties at individual 2016 Olympic Games finals in elite rhythmic gymnasts - Hodžic, A.; Vranesic-Hadzimehmedovic, D.; Šebic, L.; Turkovic, B.; Doder, I.; Mašic. M.; Ormanovic, S. (Homosporticus, 2018)
The main aim of this study was to analyze the body difficulties in the compositions of individual elite rhythmic gymnasts at the Olympic Games 2016. In the final competition, ten gymnasts competed with four apparatus: hoop, ball, clubs, and ribbon. The research data have been collected using video recorded tape during the final competitions at the Olympic Games of 2016. Two independent analyst used form of notation to diverse the elements. Based on review and analysis of exercises, a total of 40 compositions were analyzed, based on which it was determined that 9 different jumps, 13 different rotations and 12 different balances have been performed, with total sum of 34 body difficulties. Compositions analysis gymnasts performed a total of 355 difficulties that consisted of 118 rotations, 125 jumps and 112 balances. Most frequent elements were Jete with a turn (n=44), Rotation in penché (n=29) and Back scale leg high up (n=28). Finalists of the Olympics 2016 used similar body difficulties with no diversity at the choice of body difficulties which were the part of their compositions.